Penyelesaian Masalah Syarat Batas dalam Persamaan Diferensial Biasa Orde Dua dengan Menggunakan Algoritma Shooting Neural Networks - Dewi Erla Mahmudah; Ratna Dwi Christyanti; Moh. Khoridatul Huda; Fidia Deny Tisna Amijaya (LPPM STMIK Widya Utama, 2017)
The problem of initial values and boundary values in dif erential equations is still a problem that is not simple in finding the solution. In this research we will introduce a new method to solve the problem of boundary conditions in ordinary dif erential equations using shooting method and Neural Networks Algorithm (Shooting Neural Networks). The results of this study indicate that the solution obtained by using the shooting method is better than the method of shooting neural networks when the guess point value on the shooting method approaches the exact value. Methods of shooting neural neural networks are best used for problems with unknown exact solutions.